A survey of public central school libraries in the Division of Tarlac 1980-1981 - Sandiko, Nonelia L. (Institute of Library Science, University of the Philippines Diliman, 1981)
This survey was conducted to evaluate the present status of public central school libraries in the Division of Tarlac for the school year 1980-1981 in relation to existing standards.